Inflammasomes in Cancer Progression and Anti-Tumor Immunity - Lillo, Sebastian; Saleh, Maya (Frontiers in Cell and Developmental Biology, 2022)
The inflammasomes are critical regulators of innate immunity, inflammation and cell death and have emerged as important regulators of cancer development and control. Inflammasomes are assembled by pattern recognition receptors (PRR) following the sensing of microbial- or dan-ger- associated molecular patterns (MAMPs/DAMPs) and elicit inflammation through the oli-gomerization and activation of inflammatory caspases. These cysteinyl-aspartate proteases cleave the proinflammatory cytokines IL-1β and IL-18 into their biologically active mature form. The roles of the inflammasomes and associated pro-inflammatory cytokines vary greatly de-pending on the cancer type. Here we discuss recent studies highlighting contrasting roles of the inflammasome pathway in curbing versus promoting tumorigenesis. On one hand, the inflam-masomes participate in stimulating anti-tumor immunity, but they have also been shown to con-tribute to immunosuppression or to directly promote tumor cell survival, proliferation, and me-tastasis. A better understanding of inflammasome functions in different cancers is thus critical for the design of novel cancer immunotherapies.